The The Students Perceptions by Using Tik Tok as a Media Learning English - Wiranda Gusti Pratami Wiranda; syafryadin Syafryadin (Yayasan Karinosseff Muda Indonesia, 2023)
This study aims to find out student opinion responses to the use of the tik tok application to students majoring in English University at Dehasen Bengkulu. The researchers used a type of qualitative descriptive research. The researcher used Qualitative descriptive is a method. Problem solving is seen by describing the state of an object or objects. After that, the data is obtained based on the facts contained in the object. The analytical method used in this research is confirmation by using a descriptive analysis method. This descriptive analysis approach is to see students' opinions about the use of tick tock media as a medium for learning English. Then, the instrument used by researchers is a questionnaire used by researchers to collect data. The research used can be in the form of tables, graphs, medians, modes, averages, percents and percentage calculations, all of which are translated into descriptive analysis. The results of the study show that students strongly agree with the use of tick tock as a learning medium. the tik tok application is one of the social media applications that is in great demand by the public. Therefore, by being creative using tick tock, students are able to develop and increase students innovative power in learning English. with the tik tok application, students can be creative through short videos .